THE EFFECT OF PROFITABILITY, ASSETS STUCTURE, FIRM SIZE, AND CORPORATE GOVERNANCE ON STOCK PRICES WITH STOCK RETURNS AS MODERATION VARIABLES - Ni Putu Nina Eka Lestari; Ni Putu Desy Widiari; I Gede Eka Sanjaya Harta; Ni Putu Ayu Ira Rianti; I Made Chandra Mandira (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The focus of this research was to assess about how profitability, asset structure, firm size, and corporate governance affect stock prices, with stock returns act as a moderating variable. Multiple linear regression analysis and moderated regression analysis were utilized, with a total sample of 84 firms. The results of this analysis reveal that profitability, asset structure, firm size, and corporate governance all have simultaneously impact on stock prices. Profitability, asset structure, and firm size each have a significant impact on stock prices, however corporate governance has no effect. The moderating regression analysis results reveal that stock returns can moderate the relation between profitability and stock prices, but not the relation between asset structure, firm size, and corporate governance on stock prices.